Elaboração de um mapa acústico para a região central de Curitiba e principais vias de acesso ao centro da cidade - Andrade, Fernando Cunha de (2012)
The urban noise has been increasingly becoming a major concern for modern society. Given this, this case study aims to map the acoustic sound pressure levels in the central region of Curitiba and main access roads to the center in order to know what levels of noise exposed workers and citizens identify and areas with sound values above those allowed by law. The methodology adopted for the preparation of this research has acoustic map as a reference to NBR 10151, which establishes criteria for pressure gauges and measurement conditions. In the first phase measurements were made of the noise levels present in 416 points of the city center and the main access routes to it. Later raised the height of buildings across the region to prepare for the measured acoustic map through software CadnaA. The results were compared to Ordinary Curitiba Municipal Law No. 10,625, of December 19, 2002, which states that during the daytime (07h01min 19:00 until) limit sound pressure level is 65dB (A) for the central zone. In conclusion it was found that all points of measurement are above the limit allowed by local law. Thus actions are recommended simple and straight forward as using hybrid engines for trucks and bus fleets.